Prognostic Significance of Interim 11C-Methionine PET/CT in Primary Central Nervous System Lymphoma. (August 2018) - Ahn, Seo-Yeon; Kwon, Seong Young; Jung, Sung-Hoon; Ahn, Jae-Sook; Yoo, Su Woong; Min, Jung-Joon; Bom, Hee-Seung; Ki, So Yeon; Kim, Hyeoung-Joon; Lee, Je-Jung; Song, Sang Yun; Yang, Deok-Hwan
Abstract : Purpose: Primary central nervous system lymphoma (PCNSL) has a poor prognosis. There has been limited study evaluating the role of interim PET/CT in PCNSL. This prospective study investigated the interim response using sequential brain PET/CT with 11 C-methionine ( 11 C-MET) to provide prognostic information during the treatment of PCNSL. Materials and Methods: A total of 26 immunocompetent patients recently diagnosed with PCNSL were evaluated. Brain MRI and 11 C-MET PET/CT were performed at the time of diagnosis and after 4 cycles of high-dose methotrexate-based induction chemotherapy. Tumor-to-normal tissue (T/N) ratio and MTV were used to assess the interim response. Results: All patients had diffuse large B-cell lymphoma. No differences were observed in initial tumor volume or quantitative uptake among the International Extranodal Lymphoma Study Group groups. Higher International Extranodal Lymphoma Study Group risk scores were associated with higher median values for interim MTV and T/N ratios, as well as poor outcomes. After a median follow-up of 21 months, interim 11 C-MET PET/CT assessments based on the quantitative T/N ratio and MTV predicted progression-free survival and overall survival, respectively. A high interim T/N ratio was significantly associated with decreased progression-free survival (hazards ratio, 3.68; P = 0.044). Conclusions: Response assessments based on interim 11 C-MET PET/CT could predict the therapeutic outcome of PCNSL.